Pengaruh Penerapan Model Discovery Learning Terhadap Kemampuan Pemecahan Masalah Matematis Peserta Didik Kelas VIII SMPN 1 Batang Anai - ALFAZRI REFANJI . (Jurnal Edukasi dan Penelitian Matematika, 2019)
Problem solving is an important ability that must be developed by students. However, students mathematical problem solving ability in grade VIII of SMPN 1 Batang Anai is very low. The solution is the discovery learning model with students who apply conventional learning model. This type of research is a quasi experimental research design with randomized control group only design. The sample is taken with simple random sampling, class VIII 2 as an experimental class and class VIII 1 as a control class. The conclusion from the results of this study is the mathematical problem solving ability of students who apply the discovery learning model better than students who apply the coventional model in grade VIII of SMPN 1 Batang Anai. Keyword – Mathematical Problem Solving Ability, Discovery Learning